Caribbean Report 03-02-1993 - Jarvis, Mike (anchor); Grant, Eddie (interviewee); Leggett, Jeremy (interviewee); Ellis, John (interviewee); Knight, K. D. (interviewee); Kaufman, Gerald (interviewee); Patterson, P. J. (interviewee); Pickersgill, Robert Dixon (interviewee); Allen, Gary (correspondent); Osborne, John (interviewee); Eggar, Tim (interviewee) (The British Broadcasting Corporation, 1993)
The environmental pressure group – Green peace is urging Caribbean insurance companies to join its lobby against fossil fuels. In an interview with correspondent Mike Jarvis, Dr. Jeremy Leggett - geologist and environmental campaigner for Greenpeace warns of the dangers climate related losses caused by fossil fuel.John Ellis – CBE Chairman and CEO of Fyffes wholesale group in an interview with Mike Jarvis reported a 5% increase in pre tax profits. Mr. Ellis also noted that Caribbean regional profit bananas contributed significantly to this year’s growth despite more difficult trading conditions. Jamaica’s National Security Minister K.D. Knight has hit back at the British Opposition Labour Party for its stance on Jamaica’s death penalty. In response Snr. British MP Gerard Kauffman – says it’s not just the death penalty issue but also the inhumane amount of time that inmates spend on death row. The Jamaican Daily Gleaner Newspaper red headlines - “Sex Talk by Phone” created a sex talk row scandal between Jamaican Prime Minister PJ Patterson and Robert Dixon Pickersgill (aka Booby Pickersgill) – Public Utilities Minister Jamaica regarding granting a proposed license for an adult entertainment network - correspondent Gary Allen reports. John Osborne Former Chief Minister of Montserrat has resumed his criticisms of the British Governor after being been acquitted of corruption and conspiracy charges. He says that the investigation by Scotland Yard was part of a British Government attempt to get rid of him. He also stated race politics against Montserrat was an issue. Tim Eggar – British Foreign Office Minister defends the British Government’s stance on the allegations and Britain’s relationship with its dependent territories. Internationally renowned Guyanese born pop star Eddie Grant is recovering in a Georgetown hospital after falling critically ill while on vacation with his mother.
Headlines with anchor Mike Jarvis (00:00-00:30)
1. The environmental pressure group – Green peace is urging Caribbean insurance companies to join its lobby against fossil fuels (00:31-03:29).
2. John Ellis – CBE Chairman and CEO of Fyffes wholesale group in an interview with Mike Jarvis reported a 5% increase in pre tax profits (03:30 -06:45).
3. Jamaica’s National Security Minister K.D. Knight has hit back at the British Opposition Labour Party for its stance on Jamaica’s death penalty (06:46-10:09).
Keywords: Environmental responsibility--Caribbean Area.; Offenses against the environment--Caribbean Area.; Bananas—Commerce--Caribbean Area.; Capital punishment—Jamaica.; Punishment in crime deterrence--Jamaica.; Politics and government—Jamaica.; Criminal law—Jamaica.; Jamaica--Politics and government.; Elections--Jamaica.; Press—Jamaica--Politics and government.; Press—Jamaica--Elections.; Montserrat--Politics and government.; Montserrat--Politics and government--Corrupt practices.; Popular culture—Guyana--Music.; Grant, Eddie.